Legal Protection for Victims of Theft through a Restorative Justice Approach - Ririnda Agustina; Gio Griptoni (Verdict: Journal of Law Science, 2026)
The protection of theft victims in Indonesia remains vulnerable when criminal procedure is oriented mainly toward punishment and case termination. Previous studies have generally examined restorative justice as institutional policy or as ordinary case settlement, but they have not yet formulated operational victim-protection safeguards for theft cases across the police, prosecution, and court stages; this gap constitutes the novelty of this study. This article examines how restorative justice can be constructed as a victim-oriented mechanism for theft cases without reducing criminal accountability to mere private settlement. Using normative legal research, this study applies statutory, conceptual, and prescriptive approaches to Indonesian criminal law, victim protection law, police restorative justice rules, prosecutorial and judicial restorative justice policies, and contemporary literature on restorative justice. The research finds that restorative justice in theft cases is legally acceptable only when it satisfies material and formal safeguards, especially voluntary peace, fulfillment of victims’ rights, return of property, compensation, repair of damage, and verified offender responsibility. However, victim protection is weakened when restorative justice is treated as an administrative tool for case disposal rather than a structured process of recovery. The article proposes a four-layer victim protection model consisting of preventive screening, restorative recovery, corrective procedural safeguards, and post-agreement supervision. This model recognizes victims as rights holders while ensuring restorative justice in theft cases aligns with legal certainty, proportionality, and substantive justice.